PENERAPAN VISUALISASI DATA TERHADAP KLASIFIKASI TINDAK KRIMINAL DI INDONESIA - Madyatmadja, Evaristus Didik; Ridho, Muhammad Nuha; Pratama, Adhyaksa Rizky; Fajri, Miftahul; Novianto, Lutfi (ISTEK WIDURI, 2022)
Crime still occurs in every region in Indonesia. Various classifications of crimes that occur and cause unrest for people in every region in Indonesia. The purpose of this study is to analyze and visualize data on crimes that occur in every region in Indonesia so as to facilitate the Indonesian government in making decisions. The method used for this research is the clustering method. The clustering stage is carried out by grouping data on crimes that occur in Indonesia which are classified from each region. The results of the data that have been visualized show that the crime rate in each area is different according to the classification of crime, so it is necessary to increase security in each area that has a level of criminality data according to the classification of crime.